Clinical characteristics of patients assessed within an Improving Access to Psychological Therapies (IAPT) service: results from a naturalistic cohort study (Predicting Outcome Following Psychological Therapy; PROMPT). Issue 1 (December 2016) - Hepgul, Nilay; King, Sinead; Amarasinghe, Myanthi; Breen, Gerome; Grant, Nina; Grey, Nick; Hotopf, Matthew; Moran, Paul; Pariante, Carmine; Tylee, André; Wingrove, Janet; Young, Allan; et al.
Abstract Background A substantial number of patients do not benefit from first line psychological therapies for the treatment of depression and anxiety. Currently, there are no clear predictors of treatment outcomes for these patients. The PROMPT project aims to establish an infrastructure platform for the identification of factors that predict outcomes following psychological treatment for depression and anxiety. Here we report on the first year of recruitment and describe the characteristics of our sample to date. Methods One hundred and forty-seven patients awaiting treatment within an Improving Access to Psychological Therapies (IAPT) service were recruited between February 2014 and February 2015 (representing 48 % of those eligible). Baseline assessments were conducted to collect information on a variety of clinical, psychological and social variables including a diagnostic interview using the Mini International Neuropsychiatric Interview (MINI). Results Our initial findings showed that over a third of our sample were not presenting to IAPT services for the first time, and 63 % had been allocated to receive higher intensity IAPT treatments. Approximately half (46 %) were taking prescribed psychotropic medication (most frequently antidepressants). Co-morbidity was common: 72 % of the sample met criteria for 2 or more current MINI diagnoses. Our initial data also indicated that 16 % met criteria for borderline personality disorder and 69 % were at high risk of personality disorder. Sixty-one percent scored above the screening threshold for bipolarity. Over half of participants (55 %) reported experiencing at least one stressful life event in the previous 12 months, whilst 67 % reported experiencing at least one form of childhood trauma. Conclusions Our results to date highlight the complex nature of patients seen within an urban IAPT service, with high rates of psychiatric comorbidity, personality disorder, bipolarity and childhood trauma. Whilst there are significant challenges associated with researching IAPT populations, we have also confirmed the feasibility of undertaking such research.